2006
DOI: 10.1177/107110070602700109
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Talar Surface Area Occupied by Screw Fixation in Ankle Fusions

Abstract: The use of additional screw fixation when performing an ankle arthrodesis does not sacrifice a major amount of the tibiotalar contact area and will most likely not affect the biologic environment needed to obtain fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…g and h Clinical appearance after failed operation. i and j Xrays 8 months after repeated ankle arthrodesis with axis correction and stabilization with two parallel screws joint do not occupy large space (16 % of articular surface only) and allow for good contact between resected articular surfaces [12]. Secondly, it seems to be logical to insert the screws from the talus to the tibia (smaller and more distal part is screwed down to the bigger and closer one)-reverse action seems to be illogical as it does not assure good stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…g and h Clinical appearance after failed operation. i and j Xrays 8 months after repeated ankle arthrodesis with axis correction and stabilization with two parallel screws joint do not occupy large space (16 % of articular surface only) and allow for good contact between resected articular surfaces [12]. Secondly, it seems to be logical to insert the screws from the talus to the tibia (smaller and more distal part is screwed down to the bigger and closer one)-reverse action seems to be illogical as it does not assure good stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle arthrodesis is increasingly performed with arthroscopic assistance [5, 6]. Uncomplicated fixation methods to maintain proper foot alignment long enough to achieve solid bone union is a major concern of many orthopedic surgeons [9, 10, 12-16]. The ideal technique for obtaining adequate fusion is based on the least amount of hardware to achieve the strongest mechanical stability while preserving the biological environment for fusion to occur.…”
Section: Discussionmentioning
confidence: 99%
“…The number of screws necessary to achieve solid fusion varies between studies. In a sawbones model study, Brodsky et al found that the addition of a third screw does not result in a major decrease in the amount of bone contact available for fusion [16]. In a composite ankle joint model, Clifford et al found no significant differences in bending stiffness between anterior plate or lateral plate fixation and the three compression screws construct, suggesting that the addition of a compression screw will considerably increase the primary bending stiffness of ankle arthrodesis [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations